2016
DOI: 10.1111/1756-185x.12927
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of golimumab in Indian patients with rheumatoid arthritis: Subgroup data from GOMORE study

Abstract: The efficacy and safety results with add-on golimumab were consistent between RA patients from India and outside India, despite high baseline disease activity in the Indian patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…In clinical trials, patient‐reported outcomes and QoL measures obtained using health‐related quality of life (HRQoL) instruments are often considered to study the impact of any intervention on RA patients 4‐8 . QoL can be calculated using several generic (EuroQoL 's Five‐Dimensional Questionnaire [EQ‐5D], Short Form [SF]‐6D, Health Utilities Index) 9 and disease‐specific questionnaires (Rheumatoid Arthritis Quality of Life) 10 .…”
Section: Introductionmentioning
confidence: 99%
“…In clinical trials, patient‐reported outcomes and QoL measures obtained using health‐related quality of life (HRQoL) instruments are often considered to study the impact of any intervention on RA patients 4‐8 . QoL can be calculated using several generic (EuroQoL 's Five‐Dimensional Questionnaire [EQ‐5D], Short Form [SF]‐6D, Health Utilities Index) 9 and disease‐specific questionnaires (Rheumatoid Arthritis Quality of Life) 10 .…”
Section: Introductionmentioning
confidence: 99%
“…Overall, the report indicates that in Indian RA patients who are treated with etanercept (which incidentally has the lowest TB reactivation based on previous data), also report a 5% rate of TB reactivation from the latent stage . In the Indian subset of golimumab development phase 3 program (GO‐MORE trial part 1), none of the patients on golimumab ( n = 105) therapy reported TB reactivation or overt TB infection …”
Section: Latent Tuberculosis In Rheumatic Disease Patients Opting Formentioning
confidence: 83%
“…66,67 In the Indian subset of golimumab development phase 3 program (GO-MORE trial part 1), none of the patients on golimumab (n = 105) therapy reported TB reactivation or overt TB infection. 68 Low predictive value and sensitivity of screening tests Mandatory screening for LTBI using TST and IGRA has reduced the risk for TB flare but has not completely eradicated it. One of the drawbacks of these tests is that their predictive value is only 1-2% for active TB development.…”
Section: Latent Tuberculosis In Rheumatic Disease Patients Opting Formentioning
confidence: 99%
“…Recently, a study evaluating efficacy and safety of GLM in patients from India had shown the drug as effective and safe in patients with systemic manifestation of rheumatoid arthritis. [ 12 ] However, there are lack of data on usage of GLM in the management of uveitis from India.…”
Section: Discussionmentioning
confidence: 99%